Dead-time and feed-forward disturbance compensation for congestion control in data networks - S. Mascolo (International Journal of Systems Science, 2003)
Two major features characterize the congestion control problem in modern data networks: (1) propagation delays, which may have an adverse impact on the stability of closed loop congestion control algorithms, and (2) time-varying available bandwidth. To deal efficiently with these issues, it is proposed to design the controller by employing both dead-time and feed-forward disturbance compensation. Dead-time compensation provides an output that quickly matches the command signal, whereas feed-forward compensation rejects the steady-state error, which is due to time-varying available bandwidth, and provides high-link utilization without large buffering. It is also shown that standard proportional-derivative-integral controllers are not effective in data networks due to large propagation delays. Finally, dead-time compensation is compared with respect to a proportional controller to illustrate major advantages of the controller proposed here.